Ohmic contact formation of gallium nitride and electrical properties improvement - Aiman, Mohd Halil (2016)
In this chapter, in order to improve the electrical conduction of Mg-doped p-type GaN contacts, enhancement of hydrogen release from GaN substrates is attempted. The electrical conduction profiles of the p-type GaN/Ni contact annealed at 573 K and 673 K for 3600 s while subjected to current flow show some improvement compared to the contact annealed without applying the current flow. From these results, it can be understood that by applying current flow through the GaN substrates during annealing process, hydrogen release form GaN substrates can be enhanced by even annealing at low temperature. To understand the mechanism of hydrogen release by applying current flow during annealing, the change in current values p-type GaN contacts during annealing has been observed. By using regression analysis and kinetic model, the electrical conduction improvement achieve by applying current flow through GaN substrate during annealing have been analysis. The results suggest that that by applying current flow during annealing and by forming a contact with material that H can diffuse into such as Pd, the H release from GaN substrate can be enhanced and the electrical conduction of p-type GaN contact can be significantly improved.